Pengaruh Mutu Pelayanan Terhadap Kepuasan Pelanggan Pada Perusahaan Mobil Honda Remaja Jaya Makassar - Roswiyanti Roswiyanti; Muhtazib Muhtazib (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
The aim of the research was to analyze and determine the influence of physical facilities (tangible), reliability, empathy, responsiveness and assurance on Honda car customer satisfaction at the Pemuda Jaya Makassar Company. The research method used in this research is a quantitative research method. Based on the results of partial analysis through Fratio testing using variance analysis, that X1, X2, X3, service towards customer satisfaction at the Pemuda Jaya Makassar company. Based on the results of the analysis carried out, it shows that the dimension of physical evidence (tangible) has a dominant influence on the level of customer satisfaction (Y partial X1 = 0.282) at the Honda "Remaja Jaya" Makassar car sales company.